Nontargeted detection of designer androgens: Underestimated role of in vitro bioassays. Issue 5 (14th May 2021) - Lund, Rachel A.; Cooper, Elliot R.; Wang, Hui; Ashley, Zoe; Cawley, Adam T.; Heather, Alison K.
Abstract: Androgens, both steroidal and nonsteroidal in nature, are among the most commonly misused substances in competitive sports. Their recognized anabolic and performance enhancing effects through short‐ and long‐term physiological adaptations make them popular. Androgens exist as natural steroids, or are chemically synthesized as anabolic androgenic steroids (AAS) or selective androgen receptor modulators (SARMs). In order to effectively detect misuse of androgens, targeted strategies are used. These targeted strategies rely heavily on mass spectrometry, and detection requires prior knowledge of the targeted structure and its metabolites. Although exquisitely sensitive, such approaches may fail to detect novel structures that are developed and marketed. A nontargeted approach to androgen detection involves the use of cell‐based in vitro bioassays. Both yeast and mammalian cell androgen bioassays demonstrate a clear ability to detect AAS and SARMS, and if paired with high resolution mass spectrometry can putatively identify novel structures. In vitro cell bioassays are successfully used to characterize designer molecules and to detect exogenous androgens in biological samples. It is important to continue to develop new and effective detection approaches to prevent misuse of designer androgens, and in vitro bioassays represent a potential solution to nontargeted detection strategies. Abstract :